Application of A Guided Inquiry Learning Model to Improve Students' Scientific Literacy Skills - Abdillah Faizin; Endang Susantini; Raharjo Raharjo (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study aims to determine the guided inquiry learning model's effectiveness in improving students' scientific literacy skills. Method: This is an experimental research with a one-group pretest-posttest design without using a control class. Results: The research results show that applying the guided inquiry learning model significantly increases students' scientific literacy. Data were analyzed using descriptive methods. Evaluation of the learning plan shows a good feasibility level in its implementation. Student learning outcomes have increased significantly, including understanding of science concepts and scientific skills. Most students progress positively in reading, understanding, and analyzing scientific information. These findings are strengthened by direct observations of students' active participation and involvement during learning. Thus, using the guided inquiry learning model positively contributes to increasing students' scientific literacy. Novelty: The novelty of this research lies in its new contribution to increasing scientific literacy by applying the guided inquiry learning model. The positive response from students to this learning model emphasizes its relevance in advancing scientific literacy. These findings show that the practical use of the guided inquiry model can improve students' understanding of concepts and scientific skills. Integrating this learning model into the learning context adds essential value to science education. The research results confirm that the effective use of the guided inquiry model can increase students' scientific literacy, making a significant contribution to preparing them to face future scientific challenges.